Monetary economics in developing countries - Ghatak, Subrata 1939-; 9 (Basingstoke : Palgrave Macmillan, 2007)
"Revised and updated in light of recent advances, Monetary Economics in Developing Countries is a text for students of economic development and international finance, and a resource for researchers." "From the outset, the authors distinguish between the role of money in the developing world from its role in the developed world. They highlight the theoretical, institutional and empirical principles of monetary economics particular developing economies, enabling the student to grasp clearly not just the basic ideas of monetary economics but also how to apply them."--BOOK JACKET.
Previous ed. : as by Subrata Ghatak, published New York, St. Martin's Press, 1995.
Includes bibliographical references and index.
Al Amin
Keywords: Monetary policy -- Developing countries; Money -- Developing countries